Analytic validation of commercially available immunoassays for the measurement of serum cobalamin and folate concentrations in pigs. (6th May 2016) - Grützner, Niels; Knabe, Darrel; Lawhorn, Bruce D.; Dominguez, Brandon; Kauffold, Johannes; Suchodolski, Jan S.; Steiner, Jörg M.
Abstract : Background: Cobalamin (vitamin B12 ) and folate (vitamin B9 ) are important for the amino acid metabolism and nucleic acid synthesis. Immunoassays for the measurement of both vitamins in serum are routinely used in people, cats, and dogs, serving as indicators for clinical disorders including cobalamin and/or folate deficiency, small intestinal dysbiosis, or inadequate dietary supply of these vitamins. The analysis of these analytes may also be clinically useful in pigs. Objective: The purpose of this study was to analytically validate immunoassays for the measurement of cobalamin and folate concentrations in porcine serum, and to determine serum cobalamin and folate concentrations in healthy newborn pigs pre‐ and postweaning. Methods: Assay validation for both vitamins included the determination of linearity, accuracy, and intra‐ and inter‐assay variability using serum samples from 10 pigs. Also, serum cobalamin and folate concentrations were compared in piglets between pre‐ and postweaning. Results: For both vitamins, observed‐to‐expected ratios for linearity and accuracy were 93.2 ± 14.3% and 100.3 ± 8.1% (mean ± standard deviation), respectively. Intra‐ and inter‐assay coefficients of variation for serum were ≤ 8.7% and ≤12.5%, respectively. Significantly higher serum cobalamin and lower folate concentrations were observed in piglets at the time of weaning than at postweaning ( P < .0061; P < .0001, respectively). Conclusions: Both immunoassays are linear, accurate, precise, and reproducible for measurement of porcine serum cobalamin and folate concentrations. Piglets differing in age by only 12 days had significantly different serum cobalamin and folate concentrations. The implications of differing serum cobalamin and folate concentrations in pigs at different stages of life should be further investigated.